Radicular Dens Invaginatus: Report of a Rare Case. (31st July 2012) - Beena, V. T.; Sivakumar, R.; Heera, R.; Rajeev, R.; Choudhary, Kanaram; Panda, Swagatika
Abstract : Dens invaginatus is a developmental anomaly resulting from invagination of a portion of crown forming within the enamel organ during odontogenesis. The invagination ranges from a slight pitting (coronal type) to an anomaly occupying most of the crown and root (radicular type). Although a clinical examination may reveal a deep fissure or pit on the surface of an anterior tooth, radiographic examination is the most realistic way to diagnose the invagination. The objective of this case presentation is to report a rare case of radicular dens in dente, which is a rare dental anomaly.